A preliminary assessment of the Nactus pelagicus species group (Squamata: Gekkonidae) in New Guinea and a new species from the Admiralty Islands - Zug, George R.; Fisher, Robert N. (Zootaxa, 2012)
The Slender-toed Geckos (Nactus) currently have four recognized species in New Guinea, and these species divide intotwo sister clades: a pelagicus clade and a vankampeni clade (Heinicke et al. 2010). The latter contains three dwarf species.The former consists of five bisexual populations, of which numerous New Guinea populations are uncharacterized no-menclaturally and lumped under the epithet ‘pelagicus.’ This report and description of a new species of the pelagicusgroup from Manus Island in the Admiralty Islands encourages us to offer a preliminary assessment of morphology and diversity in New Guinea ‘pelagicus’ populations.